Financial education and household financial decisions during the pandemic - Donghoon Lee; Daniel Mangrum; Wilbert van der Klaauw; Crystal Wang (Federal Reserve Bank of New York, 2024)
We examine the impact of financial education on credit decisions during COVID-19. The pandemic presented economic challenges, but policy responses provided opportunities for savvy borrowers. Using variation in state-mandated financial education during high school, we find that mandated borrowers reduced their credit card balances by larger amounts after stimulus checks were distributed, and were more likely to buy homes and to refinance mortgages at low rates during the pandemic. The larger credit card balance reduction was driven by middle-income areas and subprime borrowers, while prime borrowers drove mortgage refinancing. Our findings underscore the importance of financial education for economic resilience.
Keywords: D14; G51; G53; 330; financial education; high school curriculum; financial decisions; household debt; COVID-19 pandemic